Pemberdayaan keluarga melalui pemanfaatan pekarangan (family farming) sebagai dukungan dalam pencegahan stunting - Asmah Sukarta; Sartika Sahibu; Marnianti Marnianti; Hajrah Hajrah (JOURNAL of Public Health Concerns, 2026)
Background: Stunting remains a public health problem that impacts physical growth, cognitive development, and the quality of human resources. One contributing factor to stunting is limited family access to nutritious food on a sustainable basis. According to the Indonesian Ministry of Health, the results of a national survey, which serves as the primary reference for efforts to accelerate stunting reduction, recorded a decline in the national stunting prevalence, from 21.5% in 2023 to 19.8% in 2024. This indicates that the incidence of stunting in the community still requires comprehensive intervention. Utilizing home gardens through the concept of family farming is a family empowerment strategy that has the potential to improve food security and household economics. However, at the community level, yard utilization remains suboptimal due to limited family knowledge and skills. Purpose: To empower families by utilizing yards as a source of food and additional income to support stunting prevention. Method: The program was conducted in January–February 2026 in the Lawawoi Community Health Center (Puskesmas) working area. Thirty families with toddlers and yards participated. The community service team, assisted by village officials, provided outreach on the importance of empowering empty yards to be used as productive land, particularly for growing nutritious food for families. The program was implemented through education, training, hands-on family farming practice, and mentoring based on home care and integrated health posts (Posyandu). Evaluation was conducted through observation throughout the program, with mentoring and monitoring to assess improvements in participants' knowledge and skills in managing their yards to become useful land. Results: Most participants understood the nutritional needs to prevent stunting and balanced nutrition for families, and were able to recognize signs of stunting in toddlers due to malnutrition. Most participants demonstrated increased knowledge about nutrition and types of nutrient-rich plants, and understood the relationship between nutrient consumption and stunting prevention. Furthermore, most participants utilized empty yards as a source of nutritious food for their families. Conclusion: Family economic empowerment activities through the utilization of yards (family farming) have been implemented effectively and have proven to increase family independence in providing nutritious food and providing additional income through harvests and simple processed products. The integration of family farming activities with home care programs is effective in increasing knowledge, skills, and the sustainability of family yard utilization practices and contributes to supporting the Community Health Center's promotive and preventive efforts, particularly in improving family nutritional status and preventing stunting based on local foods. Suggestion: Community Health Centers and communities facilitated by the Village Government are expected to utilize yards sustainably and develop a variety of crops and processed products to increase family economic and nutritional benefits. Routine mentoring in the home care program as a promotive and preventive effort can be carried out sustainably to have a positive impact on the wider community and support communities free from stunting based on local foods. Keywords: Family empowerment; Family farming; Home care; Integrated health post; Stunting Pendahuluan: Stunting masih menjadi permasalahan kesehatan masyarakat yang berdampak pada pertumbuhan fisik, perkembangan kognitif, serta kualitas sumber daya manusia. Salah satu faktor penyebab stunting adalah keterbatasan akses keluarga terhadap pangan bergizi secara berkelanjutan. Menurut Kementerian Kesehatan Republik Indonesia, hasil survei nasional yang menjadi rujukan utama dalam upaya percepatan penurunan stunting ini mencatat penurunan prevalensi stunting nasional, dari 21.5% pada 2023 menjadi 19.8% pada 2024. Hal ini menunjukkan bahwa kejadian stunting di masyarakat masih sangat perlu untuk dilakukan penanganan secara komprehensif. Pemanfaatan pekarangan rumah melalui konsep family farming merupakan salah satu strategi pemberdayaan keluarga yang berpotensi meningkatkan ketahanan pangan dan ekonomi rumah tangga. Namun, di tingkat masyarakat, pemanfaatan pekarangan masih belum optimal karena keterbatasan pengetahuan dan keterampilan keluarga. Tujuan: Untuk memberdayakan keluarga melalui pemanfaatan pekarangan sebagai sumber pangan dan pendapatan tambahan dalam rangka mendukung pencegahan stunting. Metode: Kegiatan dilaksanakan pada bulan Januari–Februari 2026 di wilayah kerja Puskesmas Lawawoi. Melibatkan 30 orang yang merupakan keluarga dengan balita dan memiliki pekarangan rumah. Tim pengabdian masyarakat memberikan sosialisasi dengan dibantu aparatur Desa tentang pentingnya memberdayakan pekarangan rumah yang masih kosong untuk dimanfaatkan menjadi lahan produktif, terutama dalam penyediaan tanam tumbuh pangan sumber gizi keluarga. Program dilaksanakan melalui pendekatan edukasi, pelatihan, praktik langsung family farming, serta pendampingan berbasis home care dan posyandu. Evaluasi dilakukan melalui observasi selama program dilakukan dengan pendampingan dan monitoring untuk melihat peningkatan pengetahuan dan ketrampilan peserta dalam mengelola pekarangan rumah untuk menjadi lahan bermanfaat. Hasil: Sebagian besar peserta mengetahui kebutuhan gizi untuk mencegah stunting, keseimbangan gizi untuk keluarga dan dapat mengenali tanda-tanda stunting pada balita akibat kekurangan gizi. Sebagian besar peserta menunjukkan peningkatan pengetahuan tentang gizi dan jenis tanaman sumber gizi serta memahami keterkaitan konsumsi gizi dan pencegahan stunting. Sedangkan sebagian besar peserta memanfaatkan pekarangan kosong untuk dijadikan sumber pangan gizi kebutuhan keluarga. Simpulan: Kegiatan pemberdayaan ekonomi keluarga melalui pemanfaatan pekarangan (family farming) telah terlaksana dengan baik dan terbukti mampu meningkatkan kemandirian keluarga dalam penyediaan pangan bergizi serta memberikan tambahan pendapatan melalui hasil panen dan produk olahan sederhana. Integrasi kegiatan family farming dengan program kunjungan rumah (home care) efektif dalam meningkatkan pengetahuan, keterampilan, dan keberlanjutan praktik pemanfaatan pekarangan oleh keluarga dan berkontribusi dalam mendukung upaya promotif dan preventif Puskesmas, khususnya dalam peningkatan status gizi keluarga dan pencegahan stunting berbasis pangan lokal. Saran: Diharapkan kepada Puskesmas dan masyarakat yang difasilitasi Pemerintahan Desa untuk memanfaatkan pekarangan secara berkelanjutan serta mengembangkan variasi tanaman dan produk olahan sehingga dapat meningkatkan manfaat ekonomi dan gizi keluarga. Pendampingan rutin dalam program home care sebagai upaya promotif dan preventif dapat dilakukan berkelanjutan untuk memberikan dampak positif kepada masyarakat yang lebih luas dan mendukung masyarakat yang terbebas dari stunting berbasis bahan pangan lokal.